The Financial Reform in Finland. (IMF Working Papers; Working Paper ;, 1988)
This paper examines the evolution of the Finnish financial system from a restrictive system based on credit limitations and rationing to an open system which relies on indirect, market-oriented policies. The main beneficiaries are found to be the banks and those that previously had restricted access to bank credit. Two major remaining problems are the anti-savings biases associated with the generous tax treatment of household interest payments and the cartel-like system used in providing tax-free deposits to households. The paper also challenges the argument that the reform caused a loss of monetary autonomy.